ANALYSIS OF THE SOCIO-ECONOMIC IMPACT OF LOCAL PALM OIL PLANTATION LAWS ON THE WELFARE OF UNDERPRIVILEGED COMMUNITIES: A LITERATURE REVIEW ON LAND ACCESS, RESOURCE UTILISATION, AND ECONOMIC OPPORTUNITIES IN THE PALM OIL SECTOR - Gunawan Widjaja (Adisam Publisher, 2025)
This study analyses the social and economic impacts of local oil palm plantation laws on the welfare of disadvantaged communities through a literature review approach that integrates agrarian, political economy, and inclusive development perspectives. The main focus is on two dimensions: (1) land access and natural resource utilisation, where regional regulations such as spatial planning regulations and land use rights (HGU) tend to prioritise corporations, causing agrarian conflicts, marginalisation of customary land, and degradation of water and non-timber forests; and (2) economic opportunities and social welfare, including plasma-inti partnerships, CSR, and profit-sharing funds whose distribution is uneven due to local elite corruption and weak oversight. A synthesis of literature from journals, regulations, and NGO reports reveals patterns of structural inequality, in which disadvantaged communities are trapped as vulnerable labourers without long-term autonomy, even though the palm oil sector contributes significantly to the regional GDP. The conclusion emphasises the urgency of local legal reform based on participation, transparency, and distributive justice to transform palm oil into a driver of sustainable welfare.